THE APPLICATION OF E-TOURISM IN SMALL AND MEDIUM-SCALE TOURISM IN INDONESIA: A STRATEGIC MANAGEMENT VIEW - Hussein, Ananda Sabil; Widagdo, Untoro; Asriwulan, Yeni (Journal of Indonesian Economy and Business, 2010)
Tourism sector is one of stateâs income that cannot be separated from the roles of smallÂ and medium scale business unit. In accordance with the development of science andÂ technology, tourism sector cannot be separated with the application of informationÂ technology commonly called as E-Tourism. In general, E-Tourism is an application ofÂ information technology in the field of tourism in order to achieve effectiveness andÂ efficiency in promoting the tourism sectors in Indonesia. Its application in tourism sectorÂ can be used as a medium to promote virtual promotion in order to get wider markets. It isÂ also known that most of the tourists who come to Indonesia are from developed countriesÂ and they are familiar with the application of ICT. By applying E-Tourism tourists andprospective ones are able to access tourism information fast and accurately. It is beneficialÂ for small and medium-scale businessmen. The article attempts to give a description aboutÂ the effects of E-Tourism on small and medium-scale business unit in Indonesia. It isÂ expected that those involved in tourism business are able to formulate a strategicmarketing that can provide competitive advantages, while for researchers it is hoped thatÂ the article will be beneficial for future research related to E-Tourism .Keywords: Tourism, small and medium scale business unit, E-Tourism, ICT, Strategicmarketing